Ocorrencia e uso de anadenanthera colubrina (Vell.) Brenan no semiárido paraibano - Anselmo, Maria da Glória Vieira (2015)
Due to the environmental degradation, many plant species are endangered in the world. The Caatinga is one of the most affected biome in Brazil, with a number of difficulties such as: severe desertification process, continuous exploitation of natural resources and small number of protected areas. Anadenanthera colubrina (Vell.) Brenan (angico) is one of the species that has local conservation priority, given that its population has decreased because of extraction for various purposes. This studied aimed to record and analyze the knowledge and use of Anadenanthera colubrina (Vell.) Brenan in eight rural communities in the semiarid region of Paraiba, located in the municipalities of Solânea, Remígio, Cabaceiras, Congo, São Mamede and Várzea, in addition to assess the local geographical distribution of this population. Semi-structured interviews were conducted with the householders (323 informants), seeking to record information on the use and local availability of the studied species, identifying current and potential uses. In order to collect demographic information of the population of angico, we conducted surveys, recording all individuals with a stem diameter at ground level (DNS) equal to or greater than 3.0 cm, using three methods of collection: plot method, point-quadrant method and free pathway method. Thus, from the ethnobotanical data we verified that the species showed versatility due to the use citations, divided into nine categories (timber and non timber), for many different purposes: fuel, construction, technology, medicinal, among others; however the highest number of citations was for timber purposes (87%), mentioned by men; a peculiar factor was the division of these use citations into potential and current uses, which showed that the most frequent citations were for potential uses. With regards to the phytosociological parameters, for the plot method, we recorded DeR of (0.04 to 4.2); FrR of (0.21 to 9.33) and VI (0.27 to 36.18) in the communities studied, with the exception of the community of Pau D’Arco, where no individual was identified. For the point-quadrant method, DeR was (1.8); FrR (3.01); VI (14.62) in the community of Santa Rita, whereas in the community of Coelho there was no record; with the free pathway method it was possible to identify individuals in all the communities studied, totaling 694, where in most of the communities the individuals were far from the residences, which may indicate extraction of the species in the most accessible areas. Thus, it was noticed the importance attributed to A. colubrina through several citation distributed into nine use categories, however, we observed that most of the utilities mentioned by the informants, on the species, was for potential use. Timber potential had greater prominence among the use categories, so the local availability of angico needs more attention, avoiding it becomes an endangered species. The free pathway method was the most representative in number of individuals sampled.